2019
DOI: 10.1021/acsami.9b17311
|View full text |Cite
|
Sign up to set email alerts
|

Highly Exfoliated and Functionalized Single-Walled Carbon Nanotubes as Fast-Charging, High-Capacity Cathodes for Rechargeable Lithium-Ion Batteries

Abstract: Compared with traditional metal-oxide lithium-ion battery (LIB) cathodes, nanocarbon-based cathode materials have received much attention for potential application in LIBs because of their superior power density and long-term cyclability. However, their lithium-ion storage capacity needs further improvement for practical applications, and the trade-off between capacity and conductivity, when oxygen functional groups as lithium-ion storage sites are introduced to the nanocarbon materials, needs to be addressed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The 0.5BN‐CQD sample showed the largest C═O bonding ratio of 72.9% with the smallest CO bonding (16.2%) and COH bonding (10.9%) ratio, which is attributed to the catalytic effect on oxygen chemisorption by boron dopant 30 . This increased ratio of C═O bonding facilitates redox‐mediated Li + storage with high Li + acceptability, resulting in the enhancement of the energy storage performance of LIB anodes 31 . Further, the estimated atomic percentages of B and N within all samples were also calculated using the C 1s XPS data.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The 0.5BN‐CQD sample showed the largest C═O bonding ratio of 72.9% with the smallest CO bonding (16.2%) and COH bonding (10.9%) ratio, which is attributed to the catalytic effect on oxygen chemisorption by boron dopant 30 . This increased ratio of C═O bonding facilitates redox‐mediated Li + storage with high Li + acceptability, resulting in the enhancement of the energy storage performance of LIB anodes 31 . Further, the estimated atomic percentages of B and N within all samples were also calculated using the C 1s XPS data.…”
Section: Resultsmentioning
confidence: 97%
“…30 This increased ratio of C═O bonding facilitates redox-mediated Li + storage with high Li + acceptability, resulting in the enhancement of the energy storage performance of LIB anodes. 31 Further, the estimated atomic percentages of B and N within all samples were also calculated using the C 1s XPS data. Owing to the fixed dopant concentration, the atomic percentage of nitrogen was similar in all the samples (2.1% for N-CQD, 2.0% for 0.1BN-CQD, 2.2% for 0.5BN-CQD, and 2.0% for 1.0BN-CQD), and the atomic percentage of boron increased from 0.7% to 1.9% and 3.3% for 0.1BN-CQD, 0.5BN-CQD, and 1.0BN-CQD, respectively as the amount of boric acid increased.…”
Section: Resultsmentioning
confidence: 99%
“…TEM analyses showed that the oxidation treatment effectively reduced the bundle size of the SWCNTs (Figure a,b). The TGA results in Figure c indicate that approximately 30% of the weight loss occurred below 300 °C because of the decomposition of the functionalized moieties and highly defective SWCNTs . The increased D-band of the Ox-SWCNTs in their Raman spectra (Figure d) suggests the formation of disordered or defective carbon structures, as shown in Figure b .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Ox-SWCNTs were obtained by the oxidation of pristine SWCNT (p-SWCNT, TUBALL, and OCSiAl) powders using a modified Brodie’s method. , Subsequently, 1 g of p-SWCNT and 8 g of sodium chlorate (NaClO 3 , Sigma-Aldrich) were mixed and ground in a mortar using a pestle. Thereafter, 20 mL of fuming nitric acid (>90%, Sigma-Aldrich) was added dropwise to the mixture.…”
Section: Methodsmentioning
confidence: 99%
“…So far, the reported methods for the fabrication of oxygenrich carbon materials majorly include: (i) heating the oxygencontaining precursor at a proper temperature to retain the oxygen-containing functional groups partially, [18][19][20][21] (ii) treating carbon materials with chemical oxidants to increase the concentration of oxygen species, [22][23][24] etc. However, since neither the oxidizing ability of the oxidant nor the extent of oxidation can be easily controlled, these conventional methods could not selectively modify the surface chemistry of the carbon materials.…”
Section: Introductionmentioning
confidence: 99%